ACCESS TO FINANCE AND THE BEHAVIOR OF USING BANK CREDIT: EVIDENCE FROM MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Mardika, Dhoni Rizky Widya (UIN Salatiga, 2021)
The purpose of this study is to prove the role of financial access in improving the behavior of using bank credit with the intention of using bank credit as a mediator. A sample of 150 respondents used a purposive sampling technique. The data analysis technique used is SEM-PLS. The results of the financial access have a significant and positive effect intention of using bank credit. The intention of using bank credit also has a significant and positive impact on behavior of using bank credit. However, access to finance does not directly or indirectly affect the behavior of using bank credit. This research is useful for the government and banks in managing strategies to increase the use of bank credit for MSMEs.